Ancient engineering : selective ceramic processing in the Middle Balsas region of Guerrero, Mexico - Meanwell, Jennifer (Paris monographs in American archaeology, 2017)
This volume has two main objectives: establishing a chronology of the Middle Balsas and detailing the region's pottery production methods. The author posits that pottery intended for different functions was often deliberately made and/or decorated in ways that were chosen to make the vessels more appropriate for their intended functions.